Elaboração de um plano de gerenciamento integrado de resíduos sólidos no restaurante universitário da Universidade Federal do Rio Grande do Norte - Carneiro, Cláudia Maria de Figueiredo Moreira Leite (2011)
The concern about preservation of the environment reaches different layers and sections of global society. The environmental prior quality of our planet can only be reached through changes in the attitudes taken in relation due to the waste generated by society, this also lead involving the education sector, in example of the Superior Education Institutions where the concept of ambiental management needs to gain a growing space.In the Federal University of Rio Grande do Norte, can be found the Universitary Restaurant as an example of a Food and Nutrition Unit, it is a restaurant destined to provide services to the academic comunity with the production and distribution of meals. In this operational context the work itself aims subsidies and funds to the search of as minimal generation of residues as possible, applying environmentally correct processes and practices. The work was developed in the period of September to October of 2009 in the Universitary Campus of Federal University of Rio Grande do Norte, in the Universitary Restaurant of the referred institution. The project involved all the employees of the restaurant and used like method the action survey. The produced waste was characterized, arranged according with it s nature (organic or inorganic) classificated following the NBR ISO 14004, adapted by Kinasz (2004) that adjusts the Standards to the specific reality of Food and Nutrition Services being diagnosed an expressive amount of produced waste in the Universitary Restaurant, it can be assured that a culture of wasting is very present and exists, contributing to the rise of solid residues, damaging the environment and consequently reflecting in the costs and expenses of the Unity, a known fact that characterizes and justifies the need of a promoting and active action that leads to positive reflexes in the economic and environmental area, drafting a Plan for Integrate Management of Solid Residues on the Universitary Restaurant of Federal University of Rio Grande do Norte